THE INFLUENCE OF COMPENSATION, JOB SATISFACTION, AND WORK ENVIRONMENT ON TURNOVER INTENTION AT DHARMA KERTI TABANAN HOSPITAL - Putri, Cokorda Istri Agung Vera Nindia; Kurniawan, I Putu Handy; Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Perdana, I Gede Putra (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
The purpose of this study is to determine the effect of compensation, job satisfaction, and work environment on turnover intention. The population consisted of employees at Dharma Kerti Tabanan Hospital, with a sample of 117 respondents. The data analysis techniques used in this research are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, T Test, and F Test. Based on the research results, it can be seen that compensation has a negative and significant effect on turnover intention, job satisfaction has a negative effect and is significant to turnover intention, and the work environment has a negative and significant effect on turnover intention. Suggestions that can be given to this researcher are that Dharma Kerti Tabanan Hospital is expected to provide fair and transparent promotions to employees, always provide appropriate compensation, and always try to make employees feel satisfied and comfortable in a constructive work environment.